Assessment of the application for renewal of authorisation of Biosprint® (Saccharomyces cerevisiae MUCL 39885) as a feed additive for weaned piglets. (9th November 2020) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of the authorisation of the product Biosprint ® ( Saccharomyces cerevisiae MUCL 39885) as a feed additive for weaned piglets. Biosprint ® is composed of only viable cells of Saccharomyces cerevisiae MUCL 39885. S. cerevisiae is considered by EFSA to have qualified presumption of safety status. The applicant has provided data demonstrating that the additive currently in the market complies with the conditions of the authorisation. The FEEDAP Panel confirms that the use of Biosprint ® under the current authorised conditions of use is safe for weaned piglets, the consumers and the environment. The additive is considered as a potential skin and eye irritant and a skin and respiratory sensitiser. There is no need to assess the efficacy of Biosprint ® in the context of the renewal of the authorisation.